Clusters of Poverty Incidence and Road Networks: A Case Analysis for Eastern Visayas, Philippines - Nacion, Nelda; Pantolla, Hernan Gonzales (8ISC Abstract Proceedings, 2022)
The lowest official disaggregation in estimating poverty incidence in the Philippines is on the cities and municipalities level. The Philippine Statistics Authority, through their small area estimation, has released open access data for the periods of 2009, 2012, and 2015 poverty estimates for all the cities and municipalities of the country. This study selected the region of Eastern Visayas, being one of the poorest regions in the country and currently has the slowest economic growth in the Visayas group of islands. For all three periods, the Geographical Information System was applied to generate poverty maps that led to easier visualization and interpretability. Spatial analysis was also applied to determine if clusters of poverty exist. The findings through the Moran’s I Statistic reveal that poverty incidence for all three periods of estimation has significant nonrandom clustering patterns. Moreover, the paper highlights how good road networks in the region could be instrumental in hopes of successful devolution in the future. This study, therefore, further emphasizes the importance of data-driven decision-making and the application of empirical methods in formulating and improving policies, especially those related to infrastructure investments. Keywords : Eastern Visayas, Geographical Information System, Poverty Incidence, Road Networks, Spatial Analysis